Project management case study - development of iron ore processing plant / Yap Park Wah - Yap , Park Wah (2022)
Project management is an adaptive and practical approach to be implemented for any project conducted by any organization despite the industry, size and sector. It’s the project manager’s responsibility to identify the project problem statement at hand and adapt the appropriate project management approach to guide the project to success. In this dissertation, as a part of the project team, the author aimed to develop the iron ore processing plant using project management approaches within the allocated budget and time. Apart from setting the project planning framework, the project team were tasked to monitor the project changes that occurred throughout the project execution time frame. In this case study, the author investigated the project management framework and methodology applied in the identified project integration management. The project team analyzed and constructed the project charter, management plan, project scope and cost to outline the project schedule required for project initiation. Project controlling were conducted with the aid of project management software to ensure the project was executed efficiently. Engineering design process were implemented during the project change proposed by the engineering team to increase the efficiency of the iron ore processing plant. As a result, it can be concluded that the ongoing project conducted by the project team is on track for success due to the effective project management approaches implemented.